Letter from the Editor: A time of editorial transition and reflection on spaces, leadership, partnerships and inclusivity in Swedish education - Nolan, Shaun (Educare, 2025)
The current issue features a total of eleven articles, offering a rich and diverse exploration of contemporary educational themes. Among these, nine are research articles that explore a wide range of topics, reflecting the dynamic and multifaceted nature of education in Sweden today. In addition, the issue includes one position article that presents a thought-provoking perspective on university-school research partnership work, and one book review essay that critically engages with a recent book on the economic governance of public welfare institutions, including schools. The contributions collectively address key areas such as the design and significance of educational spaces, the tension between political and educational leadership, and the evolving partnerships between universities and schools. They also explore inclusive education practices and the importance of reflective pedagogy in fostering meaningful learning experiences. Together, these articles provide valuable insights for educators, researchers, and policymakers, contributing to ongoing conversations about how to enhance educational practice and policy in diverse contexts.